Gas Sensing Mobile Robot: A Review - Visvanathan, R.; Kamarudin, K.; Mamduh, S.M.; Yeon, A.S.A.; Zakaria, A.; Kamarudin, L.M.; Shukor, S.A.A.; Shakaff, A.Y.M. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Mobile robot applications are required in various hazardous fields to reduce human casualties. One of the most demanding applications is gas sensing mobile robot. Since the hazardous chemical compound is undetectable by humans, autonomous mobile gas sensors are needed. Over the past few decades, various attempts to incorporate gas sensor on mobile robots are reported. Gas source localisation and gas distribution mapping are the two mainly focused scope of research. This paper presents the earliest works and recent development in gas sensing mobile robots.